The Impact of Transcranial Direct Current Stimulation on Upper-Limb Motor Performance in Healthy Adults: A Systematic Review and Meta-Analysis - Patel, Ronak; Ashcroft, James; Patel, Ashish; Ashrafian, Hutan; Woods, Adam J.; Singh, Harsimrat; Darzi, Ara; Leff, Daniel Richard (Frontiers in Neuroscience, 2019)
Background: Transcranial direct current stimulation (tDCS) has previously been reported to improve facets of upper limb motor performance such as accuracy and strength. However, the magnitude of motor performance improvement has not been reviewed by contemporaneous systematic review or meta-analysis of sham versus active tDCS. Objective: To systematically review and meta-analyse the existing evidence regarding the benefits of tDCS on upper limb motor performance in healthy adults. Methods: A systematic search was conducted to obtain relevant articles from three databases (MEDLINE, EMBASE, and PsycINFO) yielding 3200 abstracts. Following independent assessment by 2 reviewers, a total of 86 articles were included for review, of which 37 were deemed suitable for meta-analysis. Results: Meta-analyses were performed for four outcome measures, namely: reaction time (RT), execution time (ET), time to task failure (TTF) and force. Further qualitative review was performed for accuracy and error. Statistically significant improvements in RT (effect size -0.01; 95% CI -0.02 to 0.001, p=0.03) and ET (effect size -0.03; 95% CI -0.05 to -0.01, p=0.017) were demonstrated compared to sham. In exercise tasks, increased force (effect size 0.10; 95% CI 0.08 to 0.13, p<0.001) and a trend towards improved TTF was also observed. Conclusions: This meta-analysis provides evidence attesting to the impact of tDCS on upper limb motor performance in healthy adults. Improved performance is demonstrable in reaction time, task completion time, elbow flexion tasks and accuracy. Considerable heterogeneity exists amongst the literature, further confirming the need for a standardised approach to reporting tDCS studies.